Pengaruh ekstrak tempe kacang tunggak (Vigna Unguiculata (l.) Walp) terhadap kadar malondialdehid pada tikus putih yang diinduksi karbon tetraklorida - Lola Ayu Istifiani; Irma Sarita Rahmawati; Rahma Micho Widyanto; Rahmi Nimas Sabrina (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Free radicals that accumulate in the body can cause degenerative diseases, causing oxidative stress. One of the most damaging impacts of ROS is lipid peroxidation, which produces malondialdehyde (MDA). Consuming foods substantial in antioxidant content, such as Vigna unguiculata (L.) Walp tempeh, which contains antioxidants such as phenolics and flavonoids, can help to reduce MDA levels.Objectives: The aim of this study is to determine the effects of Vigna unguiculata (L.) Walp tempeh extract to reduce MDA levels in rats induced by carbon tetrachloride (CCl4).Methods: This study used a post test only control group design on male white rats (Rattus norvegicus) on male white rats (Rattus norvegicus) induced by CCl4. The research was conducted at the Biosciences Institute Laboratory and the Dietetics and Culinary Laboratory at Brawijaya University from September to October 2022. A sample of 25 male rats was divided into 5 groups, namely negative control, positive control, and the group induced by CCl4 with variations in the administration of cowpea tempeh ethanol extract, namely 3, 6, and 9% for 7 days. After that, the rats blood was taken to analyzed the rats MDA level using a spectrophotometer at a wavelength of 532 nm. Data analysis used One Way ANOVA and continued with post hoc Dunnett t (2-sided) test at 95% CI.Results: There were significant differences in MDA level between groups (p=0,04). MDA levels were significantly (p=0,04) higher in the K+, T1, and T3 groups than in the control group (2,227±0,595). Furthermore, the MDA level in the T2 group (2,838±0,076) was not statistically different from the normal group (p>0,05).Conclusion: This study has shown that administering rats with Vigna unguiculata (L.) Walp tempeh extract has the potential to decrease MDA levels in rats induced by CCl4.Keywords Vigna unguiculata (L.) Walp Tempeh, Oxidative stress, Carbon Tetrachloride, Malondialdehyde